Case report: Early-onset Parkinson’s disease with lower limb spasticity in a new DJ-1/PARK7 patient - Fujita, Masako; Nishijima, Haruo; Katagai, Atsuko; Suzuki, Chieko; Hattori, Nobutaka; Tomiyama, Masahiko (Frontiers in Neuroscience, 2024)
Rare autosomal recessive variants in DJ-1, a causative gene for early-onset Parkinson’s disease, have been associated with a variety of clinical syndromes in a limited number of patients. Here, we report a case of a novel DJ-1 variant in a 39-year-old man with a 4-year history of parkinsonism, cognitive dysfunction, and lower limb spasticity. He was diagnosed with Parkinson’s disease. Genetic testing of the patient revealed compound heterozygous variants in the DJ-1 gene (exon 6 deletion + c.242dup), of which exon 6 deletion was a novel variant. We conclude that variants in DJ-1 should be considered possible causes of early-onset parkinsonism with spasticity and cognitive impairment, as in this case.